Azithromycin in the Treatment of Community-acquired Pneumonia in Children - N. I. Zryachkin; S. A. Khmilevskaya; O. A. Makarova; M. A. Kuznetsovа; E. Yu. Shcherbatyuk (LLC "Diagnostics and Vaccines", 2016)
We observed 31 children aged 6 months to 6 years with community-acquired pneumonia, treated as a causal treatment of azithromycin. 20 children treated Azitroks suspension, 11 children - Sumamed suspension (control group). Results of the study showed that the efficacy and safety of the drug Azitroks suspension for the treatment of community-acquired pneumonia in children is comparable to the original drug Sumamed suspension that characterizes him as a quality domestic production of generic and can be recommended for wide use in pediatric patients.